Role of Toll-Like Receptor 2 in Regulation of T-Helper Immune Response in Chronic Obstructive Pulmonary Disease - Karolina A. Sidletskaya; Tatyana I. Vitkina; Yulia K. Denisenko; Elena E. Mineeva (Canadian Respiratory Journal)
Objective. According to modern views, the differences in the clinical course of chronic obstructive pulmonary disease (COPD) are associated with certain types of T-helper (Th) immune response. Recent data have shown that toll-like receptor 2 (TLR2) is involved in the development of Th immune response. However, TLR2-mediated regulation of Th subpopulation balance in COPD needs to be elucidated. The aim of our work is to determine the mechanisms of TLR2-mediated regulation of Th immune response in COPD of varying severity. Methods. The study included 323 smokers/ex-smokers with stable COPD (GOLD I, GOLD II, and GOLD III) and 97 healthy nonsmokers (control group). Serum levels of Th1 (TNF-α and IFN-γ), Th2 (IL-4), Th17 (IL-6 and IL-17A), Treg (IL-10) cytokines, and the percentage of peripheral blood Th cells expressing TLR2 (CD4+CD282+) were assessed by flow cytometry. Serum concentrations of IL-21 (Th17) and TGF-β1 (Treg) were measured using the ELISA method. The predominant Th cytokine profile in serum was determined by calculating the ratios between levels of Th1 and Th17 cytokines. Spearman’s correlation test was performed. Results. Patients with COPD GOLD II and III with Th1 and Th17 cytokine profiles exhibited an increase in the percentage of CD4+CD282+ cells compared to the control group. In COPD GOLD I–III, positive correlations between CD4+CD282+ cell frequency and Th17 cytokine levels (IL-6, IL-17A, and IL-21) were found. In COPD GOLD I, IL-10 concentration was negatively correlated with the percentages of studied cells; in COPD GOLD II, a positive correlation between these parameters was noted. Conclusions. Enhanced TLR2 expression on CD4+ cells shifts cytokine profile toward Th17 phenotype that plays a crucial role in COPD progression. The level of TLR2 expression on peripheral blood CD4+ cells may be considered as a biomarker for diagnosing and predicting the progression of COPD.